Knowledge, attitude and practices of pregnant women for antenatal care during COVID-19 pandemic - Singh, Ajay K.; Goel, Promila K.; Kaur, Sukhmanpreet; Goel, Vishal K. (International Journal of Research in Medical Sciences, 2023)
Background: The antenatal care had suffered across the globe during COVID-19 pandemic. This study was undertaken to elicit knowledge, attitude and practices adopted by pregnant women for antenatal care during the pandemic. Methods: A cross-sectional survey was undertaken (N=126) at a purposively selected community health center Nalagarh of Solan district in north India. Self-administered pilot tested standardized questionnaire was employed. Results: 46 percent of women were in age group of 21-25 years and had secondary level of education. 60 percent were primigravida. 47 percent of pregnant women significantly undertook antenatal care from civil hospital and 33 percent availed these services from the public health facility of the level of Primary Health Centre or Community Health Centre, χ2 (1, N=126) =7.7, p=0.02. All pregnant women had taken complete antenatal care for four times and as per schedule. Only one tested positive for the disease COVID-19. Majority of the pregnant women studied were asymptomatic. The participants had the knowledge about symptoms of disease and COVID-19 appropriate behavior. About 25 percent also had difficulty in approaching the public health sector due to lack of accessible transportation. 18 and 33 percent of pregnant women suffered from stress and anxiety respectively. All undertook iron and folic acid along with tetanus prophylaxis. 21 and 18 percent practiced wearing of face mask and frequent hand washing with soap respectively. Conclusions: COVID pandemic did not hinder antenatal care adopted by pregnant women. Lockdown and isolation were important perceived worrisome aspects of the disease.